Shear wave elastography of the placenta in patients with gestational diabetes mellitus. (3rd July 2016) - Yuksel, Mehmet Aytac; Kilic, Fahrettin; Kayadibi, Yasemin; Alici Davutoglu, Ebru; Imamoglu, Metehan; Bakan, Selim; Mihmanli, Ismail; Kantarci, Fatih; Madazli, Riza
Abstract : To evaluate placental elasticty in women with gestational diabetes mellitus (GDM) and non-diabetic controls. Thirty-three pregnant women with GDM according to the current criteria of the American Diabetes Association and 43 healthy pregnant women who were admitted to the antenatal clinic were recruited for this case–control study. Elasticity values of both the peripheral and the central parts of the placentas of the patients in both groups were determined by shear wave elastography (SWE) imaging. Mean elasticity values of both the central and the peripheral part of the placentas were significantly higher in GDM pregnancies ( p < 0.001). No difference was observed in the mean elasticity values of the central and the peripheral part of the placentas in two groups ( p > 0.05). SWE imaging technology might provide a quantitative assessment of the morphological pathologies of placentas in pregnant women with GDM.